GAMBARAN MANFAAT TERAPI BEKAM KERING TERHADAP PENURUNAN NYERI LUTUT PADA PENDERITA OSTEOARTRITIS DI PRAKTIK PERAWAT MANDIRI LATU USADHA - Desak Made Firsia Sastra Putri (JURNAL MEDIKA USADA, 2022)
Background: Knee pain is an uncomfortable feeling, from mild, moderate, or severe which is very subjective and only people who experience it can explain and evaluate the feeling. Data obtained in May 2021 at the Latu Usadha Independent Nurse Practice as many as 21 visiting patients and 11 patients experiencing knee pain. Objective: To describe the effectiveness of dry cupping therapy on the intensity of knee pain in Osteoarthritis sufferers at the Latu Usadha Independent Nurse Practice. Methodology: Pre-Experimental Design with one group pretest-posttest design, research subjects are knee pain sufferers, non-probability sampling using purposive sampling method. Research instrument with VAS observation sheet Results: Pretest results showed moderate pain (81.8%), and severe pain at 18.2%. After being given cupping therapy the results of the posttest score were obtained with minor pain results of 100.0%, which means that there is a decrease in knee pain for patients with osteoarthritis. Conclusion: There was a decrease in the level of knee pain after being given dry cupping therapy